2008
DOI: 10.1016/j.bmcl.2008.01.060
|View full text |Cite
|
Sign up to set email alerts
|

A cell-penetrating peptidic GRP78 ligand for tumor cell-specific prodrug therapy

Abstract: Tumor targeting peptides are promising vehicles for site-directed cancer therapy. Pep42, a cyclic 13-mer oligopeptide that specifically binds to glucose-regulated protein 78 (GRP78) and internalized into cancer cells, represents an excellent vehicle for tumor cell-specific chemotherapy. Here, we report the synthesis and evaluation of Pep42-prodrug conjugates that contain a cathepsin B-cleavable linker, resulting in the traceless release of drug inside the cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 16 publications
1
63
0
Order By: Relevance
“…For example, Artemisinin is a natural product isolated from Artemisia annua L. Oh et al reported that the artemisininpeptide conjugates showed potent anticancer activity against Molt-4 leukemia cells with a significantly improved cancer/normal cells selectivity (26). Pep42, a cyclic 13-mer oligopeptide that specifically binds to glucose-regulated protein 78 (GRP78) and internalizes into cancer cells, represents an excellent vehicle for tumor cell-specific chemotherapy (27). In addition, the non-immunogenicity of micro-peptides, especially of dipeptides and tripeptides, shows biological effects and ensures that consumers are free of anaphylaxis (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Artemisinin is a natural product isolated from Artemisia annua L. Oh et al reported that the artemisininpeptide conjugates showed potent anticancer activity against Molt-4 leukemia cells with a significantly improved cancer/normal cells selectivity (26). Pep42, a cyclic 13-mer oligopeptide that specifically binds to glucose-regulated protein 78 (GRP78) and internalizes into cancer cells, represents an excellent vehicle for tumor cell-specific chemotherapy (27). In addition, the non-immunogenicity of micro-peptides, especially of dipeptides and tripeptides, shows biological effects and ensures that consumers are free of anaphylaxis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics targeting GRP78 have recently emerged and have shown anti-tumor activity in solid tumors. 16,[51][52][53][54] Whether these and other agents capable of suppressing GRP78 expression or activity can be applied for suppression of leukemogenesis warrants vigorous investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it presents an effective prodrug-conjugated vehicle for a large number of cytotoxic drugs in order to accurately target neoplasm [Yoneda et al, 2008]. For instance, by means of cellular uptake and intracellular trafficking, its conjugate with taxol promotes apoptosis of tumor cells, especially the highly metastatic ones [Arap et al, 2004].…”
Section: Targeting Grp78 Therapeuticsmentioning
confidence: 99%